Impact of gravity and inertia on stable displacements of DNAPL in highly permeable porous media. (April 2022) - Cochennec, Maxime; Davarzani, Hossein; Davit, Yohan; Colombano, Stéfan; Ignatiadis, Ioannis; Masselot, Guillaume; Quintard, Michel
Abstract: The flow of Dense Non-Aqueous Phase Liquid (DNAPL) in highly permeable porous media is characterized by a complex interplay between surface tension, viscous, gravity, and inertia forces. Gravitational effects in these systems have been particularly studied in the context of displacement instability, but little work has focused on the impact of gravitational and inertia forces on the stable displacement of DNAPL in highly permeable but non-fractured porous media. Here, we study the impact of the gravity and Forchheimer numbers on the stable displacement of DNAPL fronts in porous media. We first performed DNAPL injection experiments in bead packings of different sizes for different inlet flow rates and initial saturation. These experiments were accurately modeled using a Darcy–Forchheimer model combined with an Arbitrary Lagrangian–Eulerian tracking of the DNAPL front. Once validated against stable injections in glass beads, the model was then used to perform a broader parametric study than available with our experimental setup. We explored different injection and pumping scenarios over a range of dimensionless numbers. We found that gravity can significantly alter the fluid front in flows commonly found in contaminant hydrology. We estimate, however, that inertia will have a non-negligible impact upon the displacement of DNAPL only during active remediation techniques (e.g., free product pumping method) or pipe rupture events involving low-viscous DNAPL in highly-permeable porous media.